PERIODS OF TEACHING PRONUNCIATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the period of teaching pronunciation in the school of children with hearing impairment, the development of oral speech and the wide use of hearing in the educational process, the material of words and phrases related to the lessons of the development of oral speech information about the planned work system to be carried out.